Differences in Otosclerotic and Normal Human Stapedial Osteoblast Properties Are Normalized by Alendronate in Vitro. (October 2014) - Gronowicz, Gloria; Richardson, Yvonne L.; Flynn, John; Kveton, John; Eisen, Marc; Leonard, Gerald; Aronow, Michael; Rodner, Craig; Parham, Kourosh
Objective: Identify and compare phenotypic properties of osteoblasts from patients with otosclerosis (OSO), normal bones (HOB), and normal stapes (NSO) to determine a possible cause for OSO hypermineralization and assess any effects of the bisphosphonate, alendronate. Study Design: OSO (n = 11), NSO (n = 4), and HOB (n = 13) cultures were assayed for proliferation, adhesion, mineralization, and gene expression with and without 10 –10 M-10 –8 M alendronate. Setting: Academic hospital. Methods: Cultures were matched for age, sex, and passage number. Cell attachment and proliferation + alendronate were determined by Coulter counting cells and assaying tritiated thymidine uptake, respectively. At 7, 14, and 21 days of culture + alendronate, calcium content and gene expression by quantitative reverse transcription-polymerase chain reaction (qRT-PCR) were determined. Results: OSO had significantly more cells adhere but less proliferation than NSO or HOB. Calcification was significantly increased in OSO compared to HOB and NSO. NSO and HOB had similar cell adhesion and proliferation rates. A dose-dependent effect of alendronate on OSO adhesion, proliferation, and mineralization was found, resulting in levels equal to NSO and HOB. All cultures expressed osteoblast-specific genes such as RUNX2, alkaline phosphatase, type I collagen, and osteocalcin. However, osteopontin was dramatically reduced, 9.4-fold at 14 days, in OSO compared to NSO. Receptor activator of nuclear factor κB ligand/osteoprotegerin (RANKL/OPG), important in bone resorption, was elevated in OSO with decreased levels of OPG levels. Alendronate had little effect on gene expression in HOB but in OSO increased osteopontin levels and decreased RANKL/OPG. Conclusions: OSO cultures displayed properties of hypermineralization due to decreased osteopontin (OPN) and also had increased RANKL/OPG, which were normalized by alendronate.